Feasibility of the assessment of cholesterol crystals in human macrophages using micro optical coherence tomography - Tanaka, Atsushi (2014)
The presence of cholesterol crystals is a hallmark of atherosclerosis, but until recently, such crystals have been considered to be passive components of necrotic plaque cores. Recent studies have demonstrated that phagocytosis of cholesterol crystals by macrophages may actively precipitate plaque progression via an inflammatory pathway, emphasizing the need for methods to study the interaction between macrophages and crystalline cholesterol. In this study, we demonstrate the feasibility of detecting cholesterol in macrophages in situ using Micro-Optical Coherence Tomography (µOCT), an imaging modality we have recently developed with 1-µm resolution. Macrophages containing cholesterol crystals frequently demonstrated highly scattering constituents in their cytoplasm on µOCT imaging, and µOCT was able to evaluate cholesterol crystals in cultured macrophage cells. Our results suggest that µOCT may be useful for the detection and characterization of inflammatory activity associated with cholesterol crystals in the coronary artery.